Energy Harvesting by Waste Acid/Base Neutralization via Bipolar Membrane Reverse Electrodialysis - Andrea Zaffora; Andrea Culcasi; Luigi Gurreri; Alessandro Cosenza; Alessandro Tamburini; Monica Santamaria; Giorgio Micale (Energies, 2020)
Bipolar Membrane Reverse Electrodialysis (BMRED) can be used to produce electricity exploiting acid-base neutralization, thus representing a valuable route in reusing waste streams. The present work investigates the performance of a lab-scale BMRED module under several operating conditions. By feeding the stack with 1 M HCl and NaOH streams, a maximum power density of ~17 W m−2 was obtained at 100 A m−2 with a 10-triplet stack with a flow velocity of 1 cm s−1, while an energy density of ~10 kWh m−3 acid could be extracted by a complete neutralization. Parasitic currents along feed and drain manifolds significantly affected the performance of the stack when equipped with a higher number of triplets. The apparent permselectivity at 1 M acid and base decreased from 93% with the five-triplet stack to 54% with the 38-triplet stack, which exhibited lower values (~35% less) of power density. An important role may be played also by the presence of NaCl in the acidic and alkaline solutions. With a low number of triplets, the added salt had almost negligible effects. However, with a higher number of triplets it led to a reduction of 23.4–45.7% in power density. The risk of membrane delamination is another aspect that can limit the process performance. However, overall, the present results highlight the high potential of BMRED systems as a productive way of neutralizing waste solutions for energy harvesting.